Estimation of corrosion resistance of curing mixtures based on coal-bearing rocks from western Donbass - Kovalenko, V.; Harkusha, V. (Розробка родовищ, 2016)
Purpose. Substantiation of possible use of coal-bearing rocks as a replacement for a part of the filler in the preparation of shotcrete for lining of mine workings in the conditions of mineralized mine water. Methods. The research is based on carrying out corrosion testing of concrete specimens by dipping them into mine water. Chemical analysis of mine waters composition has been completed. A scanning microscope was used to study the state of concrete specimens microstructure. Findings. A comparative analysis was conducted to evaluate of the cement rock resistance to mineralized water, depending on the composition of the starting components for the grouting and shotcrete mixtures is carried out. The change in the chemical composition of mine water after soaking concrete specimens in it is defined. Photographs of concrete specimens microstructure after soaking in ordinary and mineralized water for 6 and 8 months are shown. Originality. Curing mixtures based on coal-bearing rocks from Western Donbass are mineralized water resistant and can act as a quality protection from aggressive water filtrationdue to the properties of rocks used as a filler. Practical implications. The results can be used for the rational choice of the composition of the concrete mixture with the replacement of filler part with mine rock. That will enhance the long-term stability of the mine working lined by these compositions. Цель. Обоснование возможности использование углевмещающих пород в качестве замены части заполнителя в процессе приготовления бетона для крепления горных выработок в условиях минерализованных шахтных вод. Методика. Работа базируется на проведении коррозионных испытаний бетонных образцов путем погружения их в шахтную воду. Выполнен химический анализ состава шахтных вод. Использован растровый микроскоп для исследования состояния микроструктуры бетонных образцов. Результаты. Выполнен сравнительный анализ оценки устойчивости цементного камня к воздействию минерализованной воды в зависимости от состава исходных компонентов для тампонажных, торкрет-бетонных и набрызгбетонных смесей. Определено изменение химического состава шахтной воды после выдержки в ней бетонных образцов. Представлены фотографии микроструктуры бетонных образцов после выдержки в нормальных условиях и минерализованной воде в течение 6 и 8 месяцев. Научная новизна. Твердеющие смеси на основе углевмещающих пород Западного Донбасса устойчивы к влиянию минерализованных вод и являются качественной противофильтрационной завесой благодаря свойствам пород, использованных в качестве заполнителя. Практическая значимость. Полученные результаты могут быть использованы для рационального подбора состава бетонной смеси с заменой части заполнителя шахтной породой, что позволит повысить длительную устойчивость горной выработки, закрепленной с использованием данных составов. Мета. Обґрунтування можливості використання вуглевміщуючих порід у якості заміни частини заповнювача в процесі приготування бетону для кріплення гірничих виробок в умовах мінералізованих шахтних вод. Методика. Робота базується на проведенні корозійних випробувань бетонних зразків шляхом занурення їх у шахтну воду. Виконано хімічний аналіз складу шахтних вод. Використаний растровий мікроскоп для дослідження стану мікроструктури бетонних зразків. Результати. Виконано порівняльний аналіз оцінки стійкості цементного каменю до впливу мінералізованої води залежно від складу вихідних компонентів для тампонажних, торкрет-бетонних і набризкбетонних сумішей. Визначено зміну хімічного складу шахтної води після витримки у ній бетонних зразків. Наведено фотографії мікроструктури бетонних зразків після витримки у нормальних умовах та мінералізованої води протягом 6 і 8 місяців. Наукова новизна. Твердіючі суміші на основі вуглевміщуючих порід Західного Донбасу достатньо стійкі до впливу мінералізованих вод та є якісною протифільтраційною завісою завдяки властивостям порід, використаних у якості заповнювача. Практична значимість. Отримані результати можуть бути використані для раціонального підбору складу бетонної суміші із заміною частини заповнювача шахтної породою, що дозволить підвищити тривалу стійкість гірничої виробки, закріпленої з використанням даних складів.